Challenges Envisioned in Online Teaching on Outbreak of COVID -19 - Sobhana, Nandyal Panduranga (Advances in Social Sciences Research Journal, 2020)
The outbreak of COVID -19 was unforeseen and it forced all the Saudi universities to close the campuses and launch online teaching. This paper focused on challenges envisioned in online teaching using Blackboard system. Analytical and descriptive methods of quantitative research was used to analyse and describe the challenges and perceptions of the faculty with regard to online teaching on blackboard, anticipating that the results would form a basis to improvise online teaching in post corona era. The sample of the study constituted 25 faculty members of the Department of English, Samtah University College, Jazan University. A closed and open-ended questionnaire was used to assess the challenges of the university faculty with regard to online teaching and online training program on blackboard. In online teaching, the faculty require digital skills, tools, and instructional strategies than in a conventional face-to-face classroom teaching. They should collaborate with each other working hands-on to integrate online teaching with instructional strategies and find effective ways to support the success of online students. It is important to note that students should be relieved from anxiety and ensured that they would actively engage themselves in online learning. Summing up this research study, the researcher has observed from the analysis of the faculty questionnaire, that the faculty were ready to accept the change from the conventional mode of teaching to modern day online teaching in the post corona era, assuming that technological issues involved are properly taken care of.